Penerapan Terapi Realitas Teknik WDEP untuk Meningkatkan Harga Diri pada WBS di PSKW Adam Dewi - Putri, Roza Elmanika; Sovitriana, Rilla (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
PSKW Adam Dewi is a forum for providing guidance, services, and social rehabilitation for prostitutes so that they are able to be independent and play an active role in social life. It’s just that most WBS do not follow existing programmes, so the goals of PSKW do not materialise. After conducting a psychological examination with clinical interviews, observation, psychological tests, and administering the Rosenberg Self esteem Scale (RSES), it is known that WBS shows behaviour in assessing himself as incapable, feeling disliked, feeling dirty, and being pessimistic about his life. The lack of effort he does, and he doesn’t want to be difficult in developing his potential. After implementing the WDEP technique of group reality therapy, it was found that there was a desire to try more and be able to think more positively. Understand the goals and good hopes of the rehabilitation carried out as capital in the future. The percentage increase in self-esteem averaged 49%.